A similarity solution for the flow and heat transfer over a moving permeable flat plate in an external free stream : case of strong injection - Merkin, J. H.; Bachok @ Lati, Norfifah; Jaradat, Mihaela Anghel; Pop, Ioan (Springer Verlag, 2013)
The previous work of Bachok et al. (Heat Mass Transf. 47:1643–1649, 2011) on the forced convection heat transfer on an isothermal moving surface in an external free stream is extended to the case when fluid injection through the surface, characterized by the parameter γ, is large. The asymptotic solution derived in this limit shows that the boundary layer has a double region structure, with an inviscid inner region of thickness O(γ) and an outer shear layer. Some further aspects of the original problem not treated in Bachok et al. (Heat Mass Transf. 47:1643–1649, 2011) are discussed as well as the analogous problem for a constant surface heat flux, where relatively small injection rates are seen to give rise to large increases in the surface temperature.